Exploring Cognitive Moral Logics Using Grounded Theory: The Case of Software Piracy - Bhal, Kanika Tandon (Journal of business ethics, 2008)
The article reports findings of a study conducted to explore the cognitive moral logics used for considering software piracy as ethical or unethical. Since the objective was to elicit the moral logics from the respondents, semi-structured in-depth interviews of 38 software professionals of India were conducted. The content of the interviews was analyzed using the grounded theory framework which does not begin with constructs and their interlinkages and then seek proof instead it begins with an area of study and allows them to emerge from that area of study. Given the objective of exploring moral logics, grounded theory seemed an appropriate choice. Results revealed that 21 respondents considered software piracy unethical whereas 17 did not. Though economic reasons formed the most fundamental logic in both the cases, an overall analysis revealed that the respondents mostly used moral justification (neutralization) for not considering software piracy unethical whereas those considering it unethical used normative (principled) logics. The interconnections among logics are analyzed and results are discussed along with the limitations of the study.